The Influence Of English Learning Animation Media On Second Grade Students At State Elementary School 122371 Pematang Siantar - Simanjuntak, Olopai; Sibarani, Imelda Sabrina; Sianipar, Posma; Aritonang, Naomi; Jenetri, Yustina; Siahaan, Windi; Sipayung, Juliana; Damanik, Wulandari; Sagita, Amanda Dwi; Simamora, Rosa (Journal of Community Research and Service, 2024)
This research is entitled "the influence of english learning animation media on second grade students at state elementary school 122371 Pematangsiantar". This research is motivated by the researcher's thinking that animation media is suitable for use by 2nd grade elementary school children. Children's interest in animation media lies in the audio-visuals displayed in animation media. This study aims to evaluate the effect of learning media on the English language skills of grade 2 elementary school students. With the development of technology and increasingly innovative teaching methods, learning media such as animated videos, interactive applications and educational games have been widely used in the language learning process. This study used a quantitative method with a quasi-experimental design, involving two groups of 2nd grade elementary school students as research samples. The experimental group was given English language learning using interactive media, while the control group was given conventional learning without additional media. The results showed that students who learned with the help of interactive media showed significant improvements in listening, speaking, reading and writing skills compared to the control group. These findings indicate that the use of interactive learning media can have a positive impact on English language learning at the primary education level. The implications of this research suggest that educators consider integrating learning media in the curriculum to increase teaching effectiveness and student learning motivation.